Peran Modal Intelektual Sebagai Variabel Moderasi Pada Pengaruh Kepemilikan Institusional, Karakteristik Komite Audit, Dan Gender Diversity Terhadap Financial Distress - Febryan Adhyassa Dharmawan; Deni Darmawati (AKUNTANSI 45, 2024)
Data from energy businesses listed on the Indonesia Stock Exchange will be used to examine the moderating effect of intellectual capital on the relationships between institutional ownership, audit committee characteristics, and financial distress. The Financial Reports and Annual Reports available on the official website of the Indonesia Stock Exchange served as the data and information source for this study. This study relies on secondary data collected throughout 2019–2021, with a total sample size of 96 drawn using a purposive sampling strategy. Logistic regression is used as the analytical model. According to the data, gender diversity contributes negatively to monetary stress. The impact of audit committee features on financial distress can be bolstered by intellectual capital, and the negative effect of gender diversity on financial distress can be amplified. Financial Distress is not exacerbated by Intellectual Capital, and neither institutional ownership nor audit committee features have a negative effect on it, as shown by the data